THE PECULIARITIES OF SOCIAL PLANNING IN POSTMODERN CULTURE - Клешня, Г. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
Abstract. The article deals with the content and form of social engineering phenomenon in postmodern culture. The transition of social engineering as a technology of creation of life from the real to the virtual space.